PERLINDUNGAN HUKUM TERHADAP HAK ISTRI DAN ANAK PASCA CERAI TALAK - Lubis, Risanna Aulia Adha (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Divorce cases are something that often occurs due to many factors, this condition causes a consequence where there are rights that must be fulfilled by the ex-husband to the ex-wife and children. This study will discuss the rights of women and children after a legal divorce. These rights are considered necessary to be discussed clearly as in the Indonesian legal system, women's rights are outlined without exception which also include the rights of children from the marriage. These obligations are things that must be fulfilled by the ex-husband after a divorce which has been guaranteed through the formulation of Supreme Court regulations, especially considering that marriage in Indonesia has been regulated in positive law and Islamic law. This study uses a normative legal approach with a type of literature study research based on laws and regulations as a source of literature. The results of this study explain that after a divorce, women's rights, including the right to a living, are guaranteed in the Marriage Law, which is also strengthened by the issuance of Perma Number 3 of 2017. In addition, it is explained that the urgency of legal protection for children, both while still in marriage and after a divorce, is very much needed to minimize the potential for undesirable things, including lack of affection, neglected children, free association, or conversely the inability of children to socialize like children in general.